2010
DOI: 10.1016/j.applthermaleng.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Determination of TDC in internal combustion engines by a newly developed thermodynamic approach

Abstract: In-cylinder pressure analysis is nowadays an indispensable tool in internal combustion engine research & development. It allows the measure of some important performance related parameters, such as indicated mean effective pressure (IMEP), mean friction pressure, indicated fuel consumption, heat release rate, mass fraction burned, etc.. Moreover, future automotive engine will probably be equipped with in-cylinder pressure sensors for continuous combustion monitoring and control, in order to fulfil the more and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…Unlike for the TDC variation, where a TDC offset resulted in ROHR deviation with the same sign in compression and expansion regions, it can be observed that for a pressure offset variation, ROHR curves feature deviations with different signs in compression and expansion regions, which coincides with the results from the Table 1. Figures 2 and 4 thus in addition to the governing equations in Section 2.3 and results generated thereof confirm the basic hypothesis of the proposed method stating that ROHR features different characteristic deviations in the compression phase and the expansion phase when subjected to the TDC and the pressure offset. This further proves the hypothesis that, considering assumption stated after Equation (18) in Section 2.3, it is possible to determine both offset simultaneously using Equations (17) and (18) It can be observed in Figure 1 that for a positive TDC offsets, ROHR curves feature negative values in the compression and the expansion phase, whereas an inverse trend is observed for negative TDC offsets. This observation confirms results, presented in the Table 2 for crank angles in compression and expansion phases.…”
Section: Qualitative Validation Of the Rohr For The Pressure And Tdc supporting
confidence: 56%
See 2 more Smart Citations
“…Unlike for the TDC variation, where a TDC offset resulted in ROHR deviation with the same sign in compression and expansion regions, it can be observed that for a pressure offset variation, ROHR curves feature deviations with different signs in compression and expansion regions, which coincides with the results from the Table 1. Figures 2 and 4 thus in addition to the governing equations in Section 2.3 and results generated thereof confirm the basic hypothesis of the proposed method stating that ROHR features different characteristic deviations in the compression phase and the expansion phase when subjected to the TDC and the pressure offset. This further proves the hypothesis that, considering assumption stated after Equation (18) in Section 2.3, it is possible to determine both offset simultaneously using Equations (17) and (18) It can be observed in Figure 1 that for a positive TDC offsets, ROHR curves feature negative values in the compression and the expansion phase, whereas an inverse trend is observed for negative TDC offsets. This observation confirms results, presented in the Table 2 for crank angles in compression and expansion phases.…”
Section: Qualitative Validation Of the Rohr For The Pressure And Tdc supporting
confidence: 56%
“…In the Figure 2 ROHR values calculated using Equation (4) are presented. Vertical red lines in compression and expansion regions represent selected integration intervals used in Equations (17) and (18), which will be kept constant for all cases in the presented paper. Integration interval in the compression phase is from −70 to −40 • CA, whereas in expansion phase it is from 90 to 120 • CA.…”
Section: Qualitative Validation Of the Rohr For The Pressure And Tdc mentioning
confidence: 99%
See 1 more Smart Citation
“…23) is calculated, varies in the range ±5°C compared to the measured value of 74°C, as illustrated in Fig.7. This feature of the applied method could give an advantage over the similar, "more accurate" methods that are designed so that they search for the values of components of the ATL in parallel, such as the method disclosed in reference [4]. In this reference there is a more detailed approach to the analysis of the expression for the change in entropy, where it is called a function of loss.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of ties between the change in entropy and relative volume changes, the terms for explicit calculation of the ATL with the statement that it is possible to achieve accuracy of 0.1 degrees on the angle of rotation of the crankshaft, have been proposed. Calculation according to the method described in [4] is not carried out by these authors, primarily because it was estimated that in the turbo engine, the required initial conditions (temperature and the gas pressure at the time of closing of the intake valve) can hardly be determined with the necessary accuracy. Another reason is that the parallel use of empirical data according to [2] and the results of calculations according to [6] show a more than satisfactory match on the basis through which a fairly realistic insight on the required ATL can be acquired.…”
Section: Introductionmentioning
confidence: 99%